Legalitas Peremponang atau Muhabet sebagai Organisasi Kemasyarakatan - Reny Heronia Nendissa (Faculty of Law, Universitas Pattimura, 2019)
This writing aims to determine Peremponang or Muhabet or with other names can be categorized as community organizations based on Law Number 7/2013 as amended by Perpu No. 2/2017 because there are still many Peremponang or Muhabet or with other names in Ambon City and Maluku Province which have not been registered as a social organization. This writing uses normative juridical research type with the statute approach and conceptual approach. The results of the study explained that Peremponang or Muhabet or by other names had in fact been there even hundreds of years ago but had not been legalized and registered as mass organizations based on statutory regulations. Suggestions from this writing are. the government must make an inventory of the existence of women or muhabet or with other names in Ambon City and Maluku Province in general and advise to register so that it is not considered illegal other than that the rights and obligations of Ormas can be carried out properly especially the government's responsibility to empower Ormas, so that community welfare can be realized through women or muhabet or with other names.